Effect of Self-cured Universal Adhesive System on Shear Bond Strengths of Conventional and Bulk-fill Composites - Ayşegül Karaarslan; İhsan Hubbezoğlu; Serra Kutlu (Cumhuriyet University, 2022)
ABSTRACT Effect of Self-cured Universal Adhesive System on Shear Bond Strengths of Conventional and Bulk-fill Composites Ihsan HUBBEZOGLU1, Serra KUTLU2, Ayşegül KARAARSLAN3 1 Sivas Cumhuriyet University, Faculty of Dentistry, Department of Restorative Dentistry, Sivas, Turkey 2 Niğde Oral and Dental Center, Niğde, Turkey 3 Sivas Oral and Dental Center, Sivas, Turkey Aim: The aim of this study was to investigate the effect of self-cured universal adhesive system on shear bond strengths of two conventional and two bulk-fill composites to dentin. Material-method: In this study, four groups were formed: two conventional condensable composites[G-aenial posterior(GC), Palfique Estelite Paste(Tokuyama)], and two bulk-fill composites[Estelite Bulk Fill Flow(Tokuyama), Beautifil Bulk Restorative(Shofu)]. Each group was divided into two subgroups; G-premio bond (control group) ve self-cured Universal Bond (Tokuyama). 32 human third molar human teeth were prepared to expose dentin surfaces. After the preparation, the teeth were randomly divided into 4 main groups and 2 subgroups (n = 8), composites were applied to the surfaces with the help of cylindrical silicone transparent mold with a diameter of 4 mm and a height of 4 mm. Results: In this study, when both adhesive systems are evaluated; the highest shear bond strength value was Palfique Estelite Paste, while the lowest shear bond strength value was Beautifil Bulk Restorative. While the difference between Palfique Estelite Paste and Estelite bulk-fill flow, Beautifil Bulk Restorative was found to be statistically significant (p<0.05), the difference with G-aenial posterior was not significant (p>0.05). The difference between G-aenial posterior and Beautifil Bulk Restorative was found to be statistically significant (p<0.05). When adhesive systems are compared; G-premio bond was found to be higher in all composite groups compared to self-cured Universal Bond, but the difference between them was statistically insignificant (p>0.05). Conclusion: While conventional composites exhibited high shear bond strengths, bulk-fill composites showed values close to these values. The self-cured adhesive system we used showed near values of shear bond strength to the light-polymerized adhesive system. In terms of bond strength self-cured adhesive systems can be recommended for use in areas where light can be difficult to reach in clinical applications. It is advisable to use self-cured adhesive systems for use in areas where light can be difficult to access in clinical applications. Keywords: shear bond strength, bulk-fill composites, self-cured adhesive systems ÖZET Geleneksel ve Bulk-fill Kompozitlerin Makaslama Bağlanma Dayanımlarına Işıksız Adeziv Sistemin Etkisi Amaç: Çalışmamızın amacı, iki geleneksel ve iki bulk-fill kompozitlerin dentine makaslama bağlanma dayanımlarına ışıksız adeziv sistemin etkisinin incelenmesidir. Materyal-metod: Çalışmamızda iki geleneksel kondanse edilebilen kompozit [G-aenial posterior(GC), Palfique Estelite Paste(Tokuyama)], kütlesel yerleştirilebilen iki bulk-fill kompozit [Estelite Bulk Fill Flow(Tokuyama), Beautifil Bulk Restorative(Shofu)] olarak 4 grup oluşturuldu. Her grup iki alt gruba ayrıldı; G-premio bond (Kontrol grubu) ve ışıksız Universal Bond (Tokuyama). 32 adet insan üçüncü molar insan dişi dentin yüzeyleri açığa çıkacak şekilde prepare edildi. Preparasyonun ardından dişler rastgele 4 ana, 2 alt gruba ayrıldı(n=8), yüzeylere 4 mm çapında ve 4 mm yüksekliğindeki silindirik silikon şeffaf kalıp yardımıyla kompozitler uygulandı. Tüm grupların makaslama bağlanma değerleri universal test cihazında ölçüldü, kuvvet birimi ise "newton" (=N) olarak kalibre edildi. Bulgular: Çalışmamızda her iki adeziv sistem kullanıldığında da, en yüksek makaslama bağlanma dayanım değerini Estelite Paste gösterirken, en düşük makaslama bağlanma dayanım değerini Beautifil Bulk Restorative göstermiştir. Estelite pasteile; Bulk-fill flow ve Beautifil Bulk Restorative arasındaki fark istatistiksel olarak anlamlı bulunurken (P<0,05), G-aenial posterior ile arasındaki fark anlamsız bulunmuştur(P>0,05). G-aenial posterior ile Beautifil Bulk Restorative arasındaki fark istatistiksel olarak önemli bulunmuştur(P<0,05). Adeziv sistemler kıyaslandığında; tüm kompozit gruplarında G-premio bond, Işıksız Universal Bonda göre daha yüksek bağlanma sağlarken, aralarındaki fark istatistiksel olarak anlamsız bulunmuştur (P>0,05). Sonuçlar: Geleneksel kompozitler, yüksek makaslama bağlanma dayanımları sergilerken, bulkfill kompozitler bu değerlere yakın değerler göstermiştir. Kullandığımız ışıksız adeziv sistem, ışıkla polimerize edilen adeziv sisteme yakın bağlanma değerleri sergilemiştir. Işıksız adeziv sistemler, klinik kullanımlarda ışığın zor olabileceği bölgelerde bağlanma dayanımı açısından kullanılması önerilebilir. Anahtar kelimeler: makaslama bağlanma dayanımı, bulkfill kompozitler, ışıksız adezivler